Assessment of Nickel and Chromium Concentrations in Black Kite (Milvus migrans) Tissues: Nickel and Chromium in Black Kite - Mahmood, Shahid; Mumtaz, Muhammad Waseem; Khatoon, Amina; Hussain, Majid; Abbas, Muhammad Nadeem (Biological Sciences - PJSIR, 2014)